2019
DOI: 10.1038/s41598-018-36636-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug repositioning for dengue haemorrhagic fever by integrating multiple omics analyses

Abstract: To detect drug candidates for dengue haemorrhagic fever (DHF), we employed a computational drug repositioning method to perform an integrated multiple omics analysis based on transcriptomic, proteomic, and interactomic data. We identified 3,892 significant genes, 389 proteins, and 221 human proteins by transcriptomic analysis, proteomic analysis, and human–dengue virus protein–protein interactions, respectively. The drug candidates were selected using gene expression profiles for inverse drug–disease relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 60 publications
1
26
0
2
Order By: Relevance
“…Healthy). [22] Similar to all bioinformatics pipelines, parameter and algorithm selection impact results, and may not be optimal even after tuning, which makes use of a black-box approach for drug repositioning less appealing.…”
mentioning
confidence: 99%
“…Healthy). [22] Similar to all bioinformatics pipelines, parameter and algorithm selection impact results, and may not be optimal even after tuning, which makes use of a black-box approach for drug repositioning less appealing.…”
mentioning
confidence: 99%
“…Also, multiple omics analysis mapped to significant pathways allows for the simultaneous detection of target genes and human proteins for their potential in specific diseases. For instance, drug candidates and human protein targets have been identified for several diseases such as dengue haemorrhagic fever [27], head and neck squamous cell carcinoma [28] and rheumatoid arthritis [29] amongst many others, using this approach. However, there are also downsides to this approach.…”
Section: Pathway Mappingmentioning
confidence: 99%
“…To identify novel and potent drug candidates, approved drugs such as lovastatin (31), chloroquine (39), prednisolone (51), balapiravir (52), and celgosivir (53) were investigated for the proof-off concept clinical trials for dengue viral infection ( Figure 5). Although the results showed that they were safe in patients with acute dengue, drugs failed to meet prior-defined trial endpoints [112][113][114][115][116]. Besides, two clinical trials conducted in Thailand and Singapore involving ivermectin (54) and ketotifen (55), the preliminary result was quite promising as phase 2 study of the drug 54 suggested a reduction in serum NS1 levels and body temperature [117].…”
Section: Figure 3 Chemical Structures Of Drugs Repurposed For Cancermentioning
confidence: 99%